OPTIMIZATION OF CLINICAL STAGES AND FACTORS IN THE FABRICATION OF FIXED PROSTHESES ON IMPLANTS TO PREVENT INFLAMMATORY COMPLICATIONS (World Bulletin of Public Health, 2025)
The Purpose Of The Study is to determine the influence of the abutment inclination angle on the strength, stability, and fixation of fixed dentures as the main factors in improving the quality of orthopedic treatment with implants.